ChemInform Abstract: Efficient Gold(I) Catalyzed Asymmetric Hydroamination of Alkenes. Issue 30 (July 2015) - Abadie, Marc‐Antoine; Medina, Lorian; Agbossou‐Niedercorn, Francine; Michon, Christophe
Abstract Review: 36 refs.